Tourists perceived value, satisfaction and loyalty toward ecotourism destination image: the case of Refarm, Kampar - Lee Yi Ling; Ain Nadiah Roslan; Karamjeet Kaur Lakbir Singh; Mohamad Luqman Hakim Mohamad Azam (2016)
The main purpose of this study is to identify the relationship of Tourists' Perceived Value, Satisfaction and Loyalty toward Ecotourism Destination Image: The Case of Refarm, Kampar. To achieve this goals there are few variables and factors that had been figured out. These variables are Tourists' Perceived Value, Satisfaction and Loyalty. The quantitative research was used and 384 respondents who ever visited Refarm, Kampar were involved in this research. The result show a significant effect of tourists' perceived value, satisfaction and loyalty on ecotourism destination image whereby destination image of Refarm was influenced primarily by tourists' satisfaction, followed by tourists' loyalty and tourists' perceived value was significantly lower.